ANALISIS YURIDIS TERHADAP PENGELOLAAN ASET BADAN KREDIT DESA PASCA BERLAKUNYA PERATURAN MENTERI DALAM NEGERI NOMOR 1 TAHUN 2016 TENTANG PENGELOLAAN ASET DESA - Ningtyas, Anindita Purnama (Jurnal Panorama Hukum, 2018)
As a backbone of the traditional economy before the nation of Indonesia's independence is the economic system Lumbung Desa and Village Bank, the growth of the economic system that is since the Dutch Indies heritage. With the development of the era, Village Lumbung and Village Bank merged into one that is in the form of Village Credit Agency (BKD) which is under supervision by OJK. This can reflect that the existence of BKD which is Lumbung Desa and Bank Desa still needed by society, especially society in Rural. But the practice is internal BKD problems, one of them is the problem of assets, assets BKD is one important element in the implementation of Savings and Loans operations as well as wealth. Assets or goods are economic potentials owned by BKD. Economic potential means financial and economic benefits that can be obtained in the future, which can support the role and function of BKD as a provider of public services to the public. Asset problems in addition to melting into one with the Village, many found in some areas that assets owned by BKD has changed hands to individuals. This is because, BKD paradigm belongs to the Village and Village Assets are the assets of the Village. The disbursement of these assets is complicated by the emergence Law No. 6 of 2014 on Villages and Regulations of the Minister of Home Affairs No. 1 of 2016 on Village Asset Management.